Equine eosinophilic keratitis in horses: 28 cases (2003–2013). Issue 12 (2nd November 2015) - Edwards, Sydney; Clode, Alison B.; Gilger, Brian C.
Key Clinical Message: This retrospective case series evaluates husbandry and environmental conditions in relation to eosinophilic keratitis in horses. While no associations were found between disease and husbandry practices or specific environmental factors such as humidity or temperature, an increased prevalence of presentation in summer months was identified in this population of horses. Abstract : This retrospective case series evaluates husbandry and environmental conditions in relation to eosinophilic keratitis in horses. While no associations were found between disease and husbandry practices or specific environmental factors such as humidity or temperature, an increased prevalence of presentation in summer months was identified in this population of horses.